The subclasses of analytic functions of complex order with application of q-der - Aini Janteng; Desmond Lee Ching Yiing; Yong Enn Lun; Jaludin Janteng (Universitas Sriwijaya, 2023)
In this article, we represent A as the of analytic functions in the open unit disk. Further, new subclasses of analytic functions of complex order utilising q-derivative operator are generated. The subclasses are symbolised by Hq,b and Iq,b . Additionally, we discover that these function classes are implicated with the Fekete-Szegö inequalities.